Moysés Vellinho (1901-1980) : o intelectual da província - Herchmann, Viviane Viebrantz (2013)
This thesis research consists of primary sources of and about Moyses Vellinho s intellectual work (1901-1980), which are availableat the DELFOS Institute PUCRS Documentation and Cultural Memory Archive and from correspondences, journals, articles, books and academic work in public historical centers in Brazil and Portugal. The main objective is to understand hisrole as an intellectual, in the development and promotion in Brazil and Portugal of the Rio Grande do Sul s culture and literature. This study intends to emphasize, through Moyses Vellinho s writings, his own perspective about literature made in Rio Grande do Sul. Considering The influence of Machado de Assis, the author of Dom Casmurro, in Moyses Vellinho s work can be noted by the latteropinions aboutthe Brazilian southern state literature and culture, while an expert of the writer s body of work.The method of research consists of a qualitative document analysis, aimingdata collection, identification, categorization and analysis of primary written records, following Paul Ricoeur s approach about practical historiography and the study of bibliographical material. Documents about Moyses Vellinho s work are included as an attachment, in order to contribute to the availability of materials about the author of Brazil South and to promote his participation in literary and cultural environment.